2020
DOI: 10.1590/1678-4685-gmb-2018-0320
|View full text |Cite
|
Sign up to set email alerts
|

The combined risk effect among BIN1, CLU, and APOE genes in Alzheimer’s disease

Abstract: Genome-wide associations studies (GWAS) are detecting new variants associated with late-onset of Alzheimer's disease (LOAD), a multifactorial neurodegenerative disorder. The variants rs744373 BIN1, rs11136000 CLU and rs3764650 ABCA7 uncovered by GWAS led to different AD pathways, such as metabolism, trafficking and endocytosis of lipids and inflammation. However, most of the association studies did not replicate these variants with significance. This could be due to a small power effect evident when these vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The CLU is located on chromosome 8p21.1 and contains nine exons. 18 A previous genome wide association study (GWAS) reported that variant in rs9331896 of CLU was significantly associated with AD in European populations, 15 suggesting that rs9331896 might be a potential polymorphism marker of neurodegenerative disease. As a result of the basically similar pathological features shared by AD and PD, they may have some common genetic modifiers/pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The CLU is located on chromosome 8p21.1 and contains nine exons. 18 A previous genome wide association study (GWAS) reported that variant in rs9331896 of CLU was significantly associated with AD in European populations, 15 suggesting that rs9331896 might be a potential polymorphism marker of neurodegenerative disease. As a result of the basically similar pathological features shared by AD and PD, they may have some common genetic modifiers/pathways.…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic markers level, several genes associated with the corpus of the oligodendrocyte ecosystem have been described as risk factors in late-onset AD [ 124 ]. In genomic association studies, the BIN1 (bridging integrator 1) gene is considered to be significantly involved in late AD behind the APOE gene [ 169 ]. It is mainly expressed in mature oligodendrocytes and white matter in rodents and humans, where it regulates membrane dynamics in the phenomena of endocytosis and membrane remodeling [ 37 ].…”
Section: Brain Markers Of Myelin In Alzheimer’s Patientsmentioning
confidence: 99%
“…The genetic component of AD risk, or genetics score, queries genetic evidence attributable to all loci identified by Ensembl (GRCh38, version 104)(8) as "gene", "pseudogene" or "ncRNA_gene" resulting in a total 60,664 loci. The score is based on evidence retrieved from both genome wide association studies (GWAS) as well as GWAS by proxy (GWAX) studies 15,16,74,[111][112][113][114][115][116][117][118][119][120][121][122][123] and quantitative trait locus (QTL) studies 40,50 (see Supp Table 3). For consistency across the different GWAS studies used, nominally significant variants (unadjusted p value < 0.05) from anywhere within a 200 kb window surrounding a given target gene's coordinates are assigned to the gene.…”
Section: Target Risk Score (Trs) Development and Processmentioning
confidence: 99%